2021
DOI: 10.31729/jnma.6644
|View full text |Cite
|
Sign up to set email alerts
|

Metronidazole Induced Cerebellar Toxicity: A Case Report

Abstract: Metronidazole is a widely used antibiotic against bacterial and protozoan infections. Even though the therapeutic use of the drug is high, it is associated with some severe side effects like neurotoxicity such as optic neuropathy, peripheral neuropathy, encephalopathy and cerebellar toxicity. We present a case of a 55-years male presented with dysarthria, who had positive cerebellar sign and magnetic resonance imaging findings suggestive of metronidazole induced cerebellar toxicity following metronidazole ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
0
0
Order By: Relevance
“…Among the 5-nitroimidazole group, only Metronidazole and Tinidazole [3] have been related to neurotoxicity, which may affect both the central and peripheral nervous system, although their mechanism is still not well understood. However, some theories have been proposed, such as that nerve damage is the result of free radicals produced during metronidazole metabolism or that metronidazole and its metabolites are capable of causing inhibition of protein synthesis, generating degeneration of nerve fibers [4] and, in rats, it was observed that the drug bound to RNA, leading to inhibition of protein synthesis and axonal damage [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 5-nitroimidazole group, only Metronidazole and Tinidazole [3] have been related to neurotoxicity, which may affect both the central and peripheral nervous system, although their mechanism is still not well understood. However, some theories have been proposed, such as that nerve damage is the result of free radicals produced during metronidazole metabolism or that metronidazole and its metabolites are capable of causing inhibition of protein synthesis, generating degeneration of nerve fibers [4] and, in rats, it was observed that the drug bound to RNA, leading to inhibition of protein synthesis and axonal damage [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…However, when used in high doses and for a prolonged period, the risk of peripheral neuropathy increases; however, this effect is usually reversible when drug therapy is interrupted. There have also been reports of cerebellar dysfunction, vestibulotoxicity, cochlear toxicity, ataxic gait, and seizures [3][4][5].…”
Section: Introductionmentioning
confidence: 99%